Role of IT Infrastructure Management in Creating Competitive Advantage for Cybernet Slash Support - Arockiasamy, Sagaya Madura Anand (2009)
The IT environment of various organizations is growing more complex every day. So organizations are focusing on a expanding their infrastructure and the smooth functioning oftheir systems .This demands new levels of control over the equipments and systems that power their business. This calls for effective IT Infrastructure management. The business productivity of an organization depends on the accessibility, security and performance of the IT services. This has led to many organizations outsourcing the IT Infrastructure management to the experts. This management report explores the IT Infrastructure management capabilities of Cybernet Slash Support (CSS). CSS is a global technology solutions provider to enterprises, consumers and technology companies. It helps its client to align Information Technology with their business objectives. CSS offers Infrastructure Operations Management Solutions for clients across the globe. The author of this report was given an opportunity to do internship in Cybernet Slash Support (CSS). During the internship period, the author of this report designed and developed a questionnaire in order to understand the Infrastructure management capabilities of CSS, the influence of ITIL best practices on the service delivery of CSS and the performance of the organization. The findings were derived from the answers to the questionnaire. These findings were instrumental in understanding the role of Infrastructure management capabilities in generating a competitive advantage for CSS.